O usuário diabético diante da doença: conhecimento, atitude e práticas de autocuidado. - Oliveira, Patrícia Simplício de (2016)
The metabolic control is considered the primary goal in the treatment of DM, for its mismanagement to determine the emergence of early chronic complications, leading to high morbidity and mortality. In this direction, so that there is proper management and control of DM, the practice of self-care is the main strategy to chain positive results, considering that the people affected and their families are responsible for over 95% of the treatment. Objectives: To characterize the profile of people with DM according to sociodemographic, clinical and laboratory variables; to identify the scores of knowledge, attitude and self-care practices of people with DM; to relate the scores of knowledge, attitude and self-care practices with the sociodemographic and clinical variables of people with DM. Method: It considers a cross-sectional study of a quantitative approach, carried out with 110 people with DM in the clinic of endocrinology at the University Hospital Lauro Wanderley, of the Federal University of Paraíba, during February to June 2015. For data collection there were used four instruments: the first was built by the researcher containing sociodemographic, clinical and laboratory variables; the second and third refer to instruments Knowledge Questionnaire (Diabetes Knowledge Questionnaire - DKN-A) and the Psychological Attitudes Questionnaire of Diabetes (Attitude Questionnaire - ATT-19); being the fourth self-care activities Questionnaire with diabetes - QAD. For data analysis, technical descriptive statistics and inferential analysis were used, considering a significance level of 95% and using the tests: Fischer exact test, chi-square and T Student. The research project was approved by the Research Ethics Committee of the University Hospital Lauro Wanderley, the Federal University of Paraíba, according CAEE 39539014.0.0000.5183. Results: The sociodemographic, clinical and laboratory characteristics increase the risk of morbidity and mortality for people studied, as well as being impediments to the achievement of self-care. It was found that 93 (84.5%) DM patients have knowledge deficit and 108 (98.2%) had negative attitudes of coping; schooling and income were statistically significant, as well as the type of self-reported DM for the acquisition of knowledge and realization of self-care. It takes place most frequently oral drug therapy; statistical significance between the sociodemographic and clinical variables. Conclusion: The study revealed that people with DM have socio-demographic, clinical and laboratory features that contribute to the increasingly early onset of complications. Moreover, it was evident that these variables can influence knowledge, attitudes and self-care activities performed by the affected individual. In addition to these features, the participants presented knowledge deficit of the disease and difficulties in coping it. On the other hand, they showed good adherence to treatment through self-care activities